2022
DOI: 10.3390/life12020245
|View full text |Cite
|
Sign up to set email alerts
|

Association of the DNA Methyltransferase and Folate Cycle Enzymes’ Gene Polymorphisms with Coronary Restenosis

Abstract: Background: In recent years, the interest in genetic predisposition studies for coronary artery disease and restenosis has increased. Studies show that polymorphisms of genes encoding folate cycle and homocysteine metabolism enzymes significantly contribute to atherogenesis and endothelial dysfunction. The purpose of this study was to examine some SNPs of genes coding for folate cycle enzymes and DNA methyltransferases as risk factors for in-stent restenosis. Methods: The study included 113 patients after sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, the MTHFR C677T gene has a polymorphism associated with hyperhomocysteinaemia. [32][33][34] In our study protocol, we did not routinely measure serum folate, vitamin B12 and gene polymorphisms, which resulted in no way to understand the interaction between them in terms of risk of cardiovascular events. Third, our sample size was small, which may have led to trial bias.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MTHFR C677T gene has a polymorphism associated with hyperhomocysteinaemia. [32][33][34] In our study protocol, we did not routinely measure serum folate, vitamin B12 and gene polymorphisms, which resulted in no way to understand the interaction between them in terms of risk of cardiovascular events. Third, our sample size was small, which may have led to trial bias.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that polymorphisms in genes encoding the folate cycle significantly contribute to atherogenesis and endothelial dysfunction [51]. For instance, in a me-ta-analysis conducted on over 87,000 participants it was found that the T allele of the 665C>T MTHFR polymorphism is a risk factor for CAD, which is partially mediated by abnormal lipid levels [52].…”
Section: Large Scale Research or Candidate Genes Approach?mentioning
confidence: 99%
“…Фолатный цикл как биохимический каскадный процесс превращения ФК в доступное для усваивания организмом производное -5-метилтетрагидрофолат -кон-тролируется MTHFR [11,12]. Вместе с тем обмен фолатов является источником одноуглеродных фрагментов (метильной группы -СН 3 ) для жизненно важных клеточных процессов: биосинтеза пуриновых нуклеотидов и превращения уридинмонофосфата в тимидилат; метилирования ДНК и РНК [13,14]. С помощью ферментов фолатного цикла клеточный яд -ГЦ -переходит в метионин [15,16].…”
Section: Introductionunclassified